(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The effects of the reaction of coordination compounds of cobalt II nitrate with 6- benzylaminopurine on the “morus alba” variety of moraceae plant were studied. 6- Benzylaminopurine is a broad-spectrum plant growth regulator, capable of rejuvenating plants, bringing plants out of dormancy, causing the formation of lateral shoots and root shoots